“Are We Theologians?”: A Practical Theology Approach to Catholic Social Teaching with Women Religious in East Africa - Sarah C. DeMarais (Journal of Moral Theology, 2022)
Catholic sisters in East Africa are a powerful force for advancing integral human development, central to the vision of Catholic social teaching (CST), but they often lack access to formal theological education. When they do participate in formation in CST, they are inspired and energized to share their learnings and connect their distinctive congregational charisms to the broader social mission of the Church. This essay presents an innovative and effective approach to teaching CST that the Loyola Institute for Ministry has developed with its Certificate in Catholic Social Teaching, an online certificate offered at both the graduate and undergraduate levels. Twenty-five sisters in East Africa have earned the certificate and applied their knowledge and skills in practical theological reflection in the service of transformative action projects for integral human development and sustainability. This essay describes the inculturated course content, online delivery, and Ignatian spiritual formation woven throughout. This project and resulting student successes illustrate how a practical theological approach that honors experience, culture, and contextuality empowers students to discern and respond to community needs in light of the Catholic social tradition.